Performance of wheat, barley and triticale as influenced by irrigation levels and terminal heat stress - Tani, Nahid Nadia; Reza, Syeda Nuzhat; Kader, Md Abdul; Hasan, Ahmed Khairul; Akter, Mst Arjina (Asian-Australasian Journal of Bioscience and Biotechnology, 2016)
Alternative winter cereals should be chosen to cope up with changing climate as wheat is facing drought stress as well as terminal heat stress and resulting drastic yield reduction. Therefore, a field experiment was carried out at the Agronomy Field Laboratory, Bangladesh Agricultural University, Mymensingh during the period from November 2012 to March 2013 to find out the performance of wheat, barley and triticale as influenced by irrigation levels and terminal heat stress. The experimental factors comprised of three factors viz. three crop species, two date of sowing (18 November sowing and 24 December sowing) and three irrigation levels (completely irrigated, irrigation till booting and irrigation till flowering). The crop species comprised of wheat (var. BARI Gom-27), barley (var. BARI Barley-2) and triticale (var. BARI Triticale-2). The experiment was laid out in randomized complete block design with three replications. Crop species in 24 December sowing received higher temperature on their reproductive stages than 18 November sowing which could be considered as terminal heat stress. All the yield, yield components and grain dimensions were influenced by crop species, date of sowing, irrigation levels and their interactions. The interaction effect of crop species, date of sowing and irrigation levels showed significant in relation to yield and yield components except number of total tillers/plant, straw yield, biological yield, harvest index and number of grains/m2. The highest 1000-grain weight and grain yield were obtained from the interaction of wheat, 18 November sowing and completely irrigated condition. Result showed that yield and yield components of wheat, barley and triticale were increased with optimum sowing and completely irrigated condition and decreased with late sowing and less irrigation condition. Compared to optimum sowing, in late sowing condition with less irrigation the yield of wheat crop was reduced drastically than barley and triticale. Asian Australas. J. Biosci. Biotechnol. 2016, 1 (3), 402-409